2024
DOI: 10.1039/d3cp03539e
|View full text |Cite
|
Sign up to set email alerts
|

N-heterocyclic carbene adsorption states on Pt(111) and Ru(0001)

Tianchi Zhang,
Sonali B. Khomane,
Ishwar Singh
et al.

Abstract: N-heterocyclic carbene ligands (NHCs) are increasingly used to tune the properties of metal surfaces. The generally greater chemical and thermal robustness of NHCs on gold, as compared to thiolate surface...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 88 publications
(141 reference statements)
0
0
0
Order By: Relevance
“…14 Consequently, there are many works focusing on the spectroscopic characterization of NHCs including benzimidazolium salts, 15,16 imidazolium salts, 17 free carbene moieties, 18 and CO 2 adducts. 19 Vibrational spectroscopies such as high-resolution electron energy loss spectroscopy (HREELS), 11,20 surface-enhanced Raman spectroscopy (SERS), 21,22 and reflection absorption infrared (IR) spectroscopy (RAIRS) 23,24 have been applied as a tool to study NHC SAMs. They are often used to monitor monolayer formation and stability, 24,25 surface chemical reactions, 26,27 and catalysis.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…14 Consequently, there are many works focusing on the spectroscopic characterization of NHCs including benzimidazolium salts, 15,16 imidazolium salts, 17 free carbene moieties, 18 and CO 2 adducts. 19 Vibrational spectroscopies such as high-resolution electron energy loss spectroscopy (HREELS), 11,20 surface-enhanced Raman spectroscopy (SERS), 21,22 and reflection absorption infrared (IR) spectroscopy (RAIRS) 23,24 have been applied as a tool to study NHC SAMs. They are often used to monitor monolayer formation and stability, 24,25 surface chemical reactions, 26,27 and catalysis.…”
Section: ■ Introductionmentioning
confidence: 99%
“…19 Vibrational spectroscopies such as high-resolution electron energy loss spectroscopy (HREELS), 11,20 surface-enhanced Raman spectroscopy (SERS), 21,22 and reflection absorption infrared (IR) spectroscopy (RAIRS) 23,24 have been applied as a tool to study NHC SAMs. They are often used to monitor monolayer formation and stability, 24,25 surface chemical reactions, 26,27 and catalysis. 28,29 While previous studies have reported on a subset of the imidazolium and benzimidazolium NHC vibrational modes, 11,30 a systematic and rigorous vibrational mode analysis of NHCs bound to gold is missing in the literature.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation